Vaccination status and prevalence of enteric viruses in internationally adopted children.Tha case of Parma, Italy - Veronesi, L.; Virdis, R.; Bizzoco, et al., S. (Acta Biomedica Atenei Parmensis, 2012)
On age basis, internationally adopted children may have begun or fully completed all required vaccinations, but official documentation from original Countries is frequently insufficient. Aims of this study were to evaluate the seroprotection rate for tuberculosis, hepatitis B, poliomyelitis and tetanus according to immunization cards in 67 children recently adopted and to test the prevalence of enterovirus on faecal specimens. Seroprotection and vaccination status were frequently inconsistent and these results confirm that immunitary surveillance is a cornerstone for the prevention of diseases for which a vaccination is available.